Blended Learning Module for English Club - Winda Trisnawati; Yahfenel Evi Fussalam; Ridho Kurniawan (Media Akademika Publisher, 2025)
Development of educational technology in era of industrial revolution 4.0 is increasing rapidly. It is showed by the need for a concept and a teaching and learning-based mechanism information technology (e-learning). Various ways to integrate technology into teaching and learning process has also given special approach in transforming process from conventional education into digital education. This research aims to produce teaching materials that can be used in Blended learning activities in extracurricular program “English Club” at STKIP Muhammadiyah Muara Bungo. The research method used research and development (R&D) method. There are some steps in this research; analyzing the needs, evaluating learning materials, designing new learning materials, validating learning materials by experts, revising learning materials, try out the learning materials to the students, and finishing the learning materials. The result showed that the validation of learning material experts was 85.4; the validation of learning media experts was 83.03; the average try out score of small group was 80.7; and the average try out score of large group was 81.4. Based on the scores, the English club textbook based blended learning is valid to be used.